The Impact of the “Certificate of Marriage Readiness” Policy on the Prevention of Early Marriage in Kotawaringin Barat District, Indonesia - Lita Ismerina; Helim, Abdul; Soeradji, Elvi (Academia Publication, 2025)
This study analyzes the impact of the Ready to Marry Certificate policy on reducing early marriage rates in West Kotawaringin. Using a quantitative method with a case study approach, this research involved prospective couples and Religious Affairs Office (KUA) officials. Data were collected through questionnaires and documentation to obtain a comprehensive picture of the effectiveness of this policy. The results showed a significant decrease in the number of marriage dispensation applications after the implementation of the policy. In addition, the policy played a role in raising public awareness of the importance of delaying marriage to a more mature age. However, policy implementation still faces a number of challenges, including a lack of coordination between relevant institutions and community resistance in some areas. This study concludes that the Surat Keterangan Siap Nikah policy has great potential to reduce the number of early marriages, but needs further improvement and adjustment to overcome the existing obstacles. The findings are expected to serve as a foundation for the development of more effective policies in the future.